2007
DOI: 10.1242/dev.02861
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of BMP4 activity by gremlin 1 enables ureteric bud outgrowth and GDNF/WNT11 feedback signalling during kidney branching morphogenesis

Abstract: Antagonists act to restrict and negatively modulate the activity of secreted signals during progression of embryogenesis. In mouse embryos lacking the extra-cellular BMP antagonist gremlin 1 (Grem1), metanephric development is disrupted at the stage of initiating ureteric bud outgrowth. Treatment of mutant kidney rudiments in culture with recombinant gremlin 1 protein induces additional epithelial buds and restores outgrowth and branching. All epithelial buds express Wnt11, and Gdnf is significantly upregulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
174
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(190 citation statements)
references
References 42 publications
(48 reference statements)
10
174
0
2
Order By: Relevance
“…The notion that BMP signalling acts pro-apoptotic may therefore seem at a first glance surprising. However, immunostaining and reporter assays indicate an absence of pSMAD signalling from early renal progenitors 47,48 . In vitro experiments suggest that BMP7 promotes progenitor proliferation via a JNK-dependent mechanism 34 .…”
Section: Discussionmentioning
confidence: 98%
“…The notion that BMP signalling acts pro-apoptotic may therefore seem at a first glance surprising. However, immunostaining and reporter assays indicate an absence of pSMAD signalling from early renal progenitors 47,48 . In vitro experiments suggest that BMP7 promotes progenitor proliferation via a JNK-dependent mechanism 34 .…”
Section: Discussionmentioning
confidence: 98%
“…A complex system for the control of BMP signaling by both BMP antagonists and agonists is therefore required. 44 These modulators are essential to BMP function, and their inactivation strongly influences the kidney's response to acute and chronic injury. 21,45 The response of the S3 segment to BMPs is of particular relevance to acute ischemic injury because this is the site of the most profound cellular damage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the temporospatial changes in both Grem1 and its target BMPs are likely to also determine whether Grem1 can drive or inhibit cell proliferation in each specific cellular context. Grem1 has been shown to bind and inhibit BMP2, BMP-4 and BMP7 in the process of limb development and in fibrosis of the lung and kidney [10,12,30,31]. In addition, recent data has shown that Grem1 acts as an agonist at the VEGFR2 receptor, triggering angiogenic sprouting of endothelial cells [15].…”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking Grem1 do not develop kidneys [10,11], likely due to an inappropriately strong drive from BMP-4 during development [11]. Deletion of one allele of BMP-4 is sufficient to rescue kidney development in grem1−/− mice, highlighting the signalling interplay between these two proteins [12]. Grem1 can also bind to precursor BMP-4 intracellularly, preventing its secretion and thus inhibiting its action at the BMP receptor [13].…”
Section: Introductionmentioning
confidence: 99%